PENGARUH CSR DISCLOSURE, KESEMPATAN BERTUMBUH DAN RISIKO KEGAGALAN PERUSAHAAN TERHADAP EARNINGS RESPONSE COEFFICIENT - Lely Indriaty; Della Tania (Akademi Akuntansi YKPN Yogyakarta, 2018)
The aims of this research are to know the influence of CSR disclosure, growth opportunities and default risk to earnings response coefficient in the manufacturing company of pharmaceutical sub sector listed on the Indonesia Stock Exchange period 2010-2015. This research belongs to quantitative research. Sample collection technique used purposive sampling. Using purposive sampling technique, 6 companies is used as research sample. The analysis method of this research used multiple linear regression analysis. The results showed that: (1) CSR disclosure has positive and significant influence to earnings response coefficient (sig t 0.0002 < 0.05), (2) Growth opportunities has positive and significant influence to earnings response coefficient (sig t 0.0169 < 0.05), (3) Default risk has negative and significant influence to earnings response coefficient (sig t 0.0045 < 0.05). Simultaneously, CSR disclosure, growth opportunities, and default risk has significant influence to earnings response coefficient (sig f 0.000000 < 0.05).